Performance Testing of Download Services of COSMC - Jiří Horák; Jan Růžička; Jiří Ardielli (Geoinformatics FCE CTU, 2013)
The paper presents results of performance tests of download services of Czech Office of Surveying, Mapping and Cadastre according to INSPIRE  requirements. Methodology of testing is explained, including monitoring performance  of reference servers. 26 millions of random requests were generated for each monitored operation, layer and coordinate system. The temporal development of performance indicators are analyzed and discussed. Results of performance tests approve the compliance with INSPIRE qualitative requirements for download services. All monitored services satisfy requirements of latency, capacity and availability. The latency and availability requirements are fulfilled with an abundant reserve. No problems in structure and content of responses were detected.